2019
DOI: 10.1080/17429145.2019.1640295
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of a PR-1 Gene,MuPR1, involved in disease resistance response in mulberry (Morus multicaulis)

Abstract: In the present study, the cDNA (designated MuPR1) of PR1 gene was obtained from mulberry. Our results showed that MuPR1 shares some conserved characteristics with its homologues from different plant families. MuPR1 was localized exclusively to the extracellular spaces, and the MuPR1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…qRT-PCR analysis revealed that the PtPRR7 gene was expressed in roots, stems, and leaves, whilst the PtPRR7 gene was the highest expression in roots. The results are in agreement with a study in mulberry (Fang et al, 2019).…”
Section: Conflict Of Interestssupporting
confidence: 92%
“…qRT-PCR analysis revealed that the PtPRR7 gene was expressed in roots, stems, and leaves, whilst the PtPRR7 gene was the highest expression in roots. The results are in agreement with a study in mulberry (Fang et al, 2019).…”
Section: Conflict Of Interestssupporting
confidence: 92%
“…However, the drawbacks of wood, such as dimensional instability when exposed to wet conditions and biological degradation when exposed to decay fungi, limit its long-term utilization [6][7][8][9][10]. Although its biodegradable nature is beneficial, from the perspective of sustainable development wood still needs to be modified to obtain better durability when exposed to the above harsh environments [11][12][13][14][15]. The durability of wood with respect to deformation in water and biological degradation due to decay fungi is essentially related to its cell wall components and microstructure [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…DC3000 (Fang et al . 2019), as well as in response to leaf rust fungal infection (Gao et al . 2014).…”
Section: Discussionmentioning
confidence: 99%